IMPLIKASI PENGGUNAAN TEKNOLOGI PESAWAT SILUMAN (STEALTH FIGHTER) DALAM KAITANNYA DENGAN KEDAULATAN SUATU NEGARA ATAS RUANG UDARA WILAYAHNYA DITINJAU MENURUT HUKUM INTERNASIONAL - Joshua P. Hutabarat; Sutiarnoto Sutiarnoto; Chairul Bariah (Journal of USU International Law, 2013)
ABSTRAK The development of technology and knowledge is one of the essential factor that gives a big impact to the development of international law. Just like the two edges blade, every development of each aspect have it: technology and knowledge or the international law it self have negative and positive impact. As we know the development of air law as one of the branch of international law study already gain enormous attention. Air law become one of the great development of international law, just like the law of sea. The existence of each states is beyond imagination before the air law was exist, with the presence of air law every states have a clear rights on airspace beyond theirs land it self. With the help of technology development, the control of air space is rely on radar technology (Radio Detection and Ranging). Radar system is using the electromagnetic pulse to detect, measure the distance and mapping the object such as aircraft position, land vehicle shape and the climate/weather changes information. As far as we can see radar technology is used as the detector to possibly illegal infiltrator aircraft to a state air space. But the development of technology aircraft give a born to a new technology, this new technology will be the antigen or opposing side of radar technology. This new technology is: Stealth Fighter system, Stealth fighter is one of the best development of military technology. Stealth fighter have ability to disappear from the detection of radar. Stealth fighter very ideal when it’s used to infiltrate an area of the state without noticeable. The presents of this technology give a threat to the air space jurisdiction of the state. In order to keep the existence of airlaw, must be there a regulation about stealth fighter it self.